factorize 4x^2(y-z) +6(z-y)
Answers
Answered by
7
4x^2(y-z)-6(y-z)
=(y-z)(4x^2-6)
=2(y-z)(2x^2-3)
=(y-z)(4x^2-6)
=2(y-z)(2x^2-3)
Answered by
11
Here is your answer > >
4x^2 (y-z)+6 (z-y)
4x^2 (y-z)-6 (-z+y)
4x^2 (y-z)-6 (y-z)
(4x^2-6)(y-z)
2 (2x^2-3)(y-z)
Hope it helps! !
4x^2 (y-z)+6 (z-y)
4x^2 (y-z)-6 (-z+y)
4x^2 (y-z)-6 (y-z)
(4x^2-6)(y-z)
2 (2x^2-3)(y-z)
Hope it helps! !
Similar questions
Accountancy,
8 months ago
Math,
8 months ago
Environmental Sciences,
1 year ago
Psychology,
1 year ago
English,
1 year ago
Chemistry,
1 year ago